Integrated approach in the control and management of skin neglected tropical diseases in three health districts of Côte d'Ivoire - Aboa Paul Koffi; Théodore Ange Kouakou Yao; Yves Thierry Barogui; Gabriel Diez; Simplice Djakeaux; Marie Hélène Zahiri; Ghislain Emmanuel Sopoh; Silvia Santos; Kingsley Bampoe Asiedu; Roch Christian Johnson; Henri Assé (BMC, 2020)
Abstract Background Neglected tropical diseases (NTDs) comprise 20 communicable diseases that are prevalent in rural poor and remote communities with less access to the health system. For effective and efficient control, the WHO recommends that affected countries implement integrated control interventions that take into account the different co-endemic NTDs in the same community. However, implementing these integrated interventions involving several diseases with different etiologies, requiring different control approaches and driven by different vertical programs, remains a challenge. We report here the results and lessons learned from a pilot test of this integrated approach based on integrated screening of skin diseases in three co-endemic health districts of Côte d'Ivoire, a West African country endemic for Buruli ulcer, leprosy and yaw. Method This cross-sectional study took place from April 2016 to March 2017 in 3 districts of Côte d'Ivoire co-endemic for BU, leprosy and yaws. The study was carried out in 6 stages: identification of potentially co-endemic communities; stakeholder training; social mobilization; mobile medical consultations; case detection and management; and a review meeting. Results We included in the study all patients with skin signs and symptoms at the screening stage who voluntarily accepted screening. In total, 2310 persons screened had skin lesions at the screening stage. Among them, 07 cases were diagnosed with Buruli ulcer. There were 30 leprosy cases and 15 yaws detected. Other types of ulcerations and skin conditions have been identified and represent the majority of cases detected. We learned from this pilot experience that integration can be successfully implemented in co-endemic communities in Côte d'Ivoire. Health workers are motivated and available to implement integrated interventions instead of interventions focused on a single disease. However, it is essential to provide capacity building, a minimum of drugs and consumables for the care of the patients identified, as well as follow-up of identified patients, including those with other skin conditions. Conclusions The results of this study show that the integration of activities can be successfully implemented in co-endemic communities under the condition of staff capacity building and minimal care of identified patients.